2015
DOI: 10.1007/s00198-015-3448-8
|View full text |Cite
|
Sign up to set email alerts
|

Swimming and bone: Is low bone mass due to hypogravity alone or does other physical activity influence it?

Abstract: Swimming may displace weight-bearing VPA with serious implications on bone health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 35 publications
3
10
0
Order By: Relevance
“…The results observed in this study are similar to those obtained by Gómez-Bruton et al, 5 who also compared swimmers with their non-athlete peers. As in the current study, the authors found that BMD results between men and women were similar, yet the BMD levels of the arms and spine of the athletes were higher than those of the non-athletes.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The results observed in this study are similar to those obtained by Gómez-Bruton et al, 5 who also compared swimmers with their non-athlete peers. As in the current study, the authors found that BMD results between men and women were similar, yet the BMD levels of the arms and spine of the athletes were higher than those of the non-athletes.…”
Section: Discussionsupporting
confidence: 91%
“…Results of the regional and total BMD of athletes of both sexes. important to emphasize that most of the studies indicated showed that swimming has negative or neutral impacts 5,15,25 on BMD.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…[ 16 ] In fact, swimming in "hypogravity" conditions has potential to decrease the bone formation because it decreases the time engaged in weight-bearing activities usually observed in the daily activities of adolescents. [ 17 18 ] Therefore, adolescents engaged in organized sports who compete at the national levels would be more exposed to these deleterious effects, because they are engaged in long routines of training during most part of the year.…”
Section: Introductionmentioning
confidence: 99%